Psychometric properties of the Dundee Ready Educational Environment Measure (DREEM) in a Moroccan sample of nursing students - Khadija, Saka; Amarouch, Mohamed-Yassine; Miyah, Youssef; Benjelloun, Mohammed; El-Hilaly, Jaouad (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: The educational environment is crucial to student learning and professional development in nursing education. The Dundee Ready Educational Environment Measure (DREEM) is a widely used tool for assessing educational environments in health professions. However, its psychometric properties have not been sufficiently evaluated in the Moroccan context, particularly among nursing students. Objective: This study aimed to examine and validate the psychometric properties of the Arabic version of the DREEM scale in a sample of Moroccan nursing students. Methods: A cross-sectional study was conducted between May and July 2023 among 445 undergraduate nursing students at the Higher Institute of Nursing Professions and Health Techniques in Meknes, Morocco. Data were collected using the Arabic-translated DREEM questionnaire. Principal Component Analysis (PCA) was conducted to assess variance distribution, while Confirmatory Factor Analysis (CFA) was used to test model fit using key indices. Reliability was measured using Cronbach’s alpha, and intra-class correlation coefficients (ICCs) were calculated for test-retest reliability. Results: PCA confirmed a five-factor structure, with the first two principal components explaining 19.13% and 23.61% of the total variance. CFA results showed that the students’ perceptions of learning (SPL) and academic atmosphere (SPA) subscales had good to acceptable fit, while the students’ perceptions of teachers (SPT) and academic self-perception (SASP) subscales demonstrated moderate to marginal fit. The Arabic DREEM scale exhibited good internal consistency, with a Cronbach’s alpha of 0.87. Sociodemographic factors, including gender, scholarship status, and rural-urban background, influenced students’ perceptions of their educational environment. Conclusion: This study confirmed the reliability and validity of the Arabic version of the DREEM scale for assessing nursing students’ educational environments in Morocco. However, variability in model fit across subscales suggests the need for further refinement to enhance cultural adaptation. Findings highlight disparities in teaching quality, academic support, and student engagement, emphasizing the importance of improving teacher-student interactions, interactive teaching methods, and social support systems to enhance learning outcomes.